INTERNATIONAL NORMALIZED RATIO AND ACTIVATED PARTIAL THROMBOPLASTIN TIME DO NOT PREDICT PLASMA TRANSFUSION IN LIVER TRANSPLANTATION - David Silveira MARINHO; Joel Avancini ROCHA FILHO; Estela Regina Ramos FIGUEIRA; Claudia Regina FERNANDES; Rui Carlos DETSCH JUNIOR; José Huygens Parente GARCIA; Wellington ANDRAUS; Luiz Augusto Carneiro D’ALBUQUERQUE (ABCD: Arquivos Brasileiros de Cirurgia Digestiva)
ABSTRACT BACKGROUND: Blood loss during liver transplantation (LT) remains a major concern associated with increased morbidity and reduced patient and graft survival. The high complexity of the procedure associated with the multifaceted origin of the bleeding urges early identification of high-risk patients and proper monitoring of hemostasis disorders in order to improve results. The accuracy of international normalized ratio (INR) and activated partial thromboplastin time (aPTT) to evaluate coagulation status in cirrhotic patients has been doubted. AIMS: The aim of this study was to investigate the applicability of these coagulation tests to indicate fresh frozen plasma transfusion in LT. METHODS: This retrospective cohort study analyzed 297 cirrhotic patients submitted to LT. INR and aPTT were measured preoperatively and in each surgical phase. Hemostatic blood components were transfused only for coagulopathy indication. Patients were divided according to intraoperative plasma transfusion into transfused and non-transfused groups. The accuracy of INR and aPTT to predict plasma transfusions was investigated. The alert values of INR and aPTT unassociated with coagulopathy in each phase of surgery were identified. RESULTS: Multivariate analysis showed that preoperative hematocrit (odds ratio [OR]=0.90, p<0.001), preoperative fibrinogen (OR=0.99, p<0.001), and absence of hepatocellular carcinoma (OR=3.57, p=0.004) were significant predictors of plasma transfusions. CONCLUSIONS: INR and aPTT demonstrated poor accuracy in predicting plasma transfusions, irrespective of the cutoff adopted, highlighting the need for a more comprehensive approach to guide hemostatic therapy in LT to improve the outcome.